Pengaruh Awan Terhadap Visibilitas Hilal di POB Blang Tiron Bukit Pole Kompleks Perumahan PT. Perta Arun Gas Lhokseumawe - Taufiq Hidayat Panjaitan; Machzumy Jafar M.Ali; Muhammad Diah (Islamic Astronomy Department, Sharia and Law Faculty, 2023)
During the month of Ramadan, Shawal, zulqaidah and zulhijjah, there were no sights of hilal due to the presence of cloud-like natural factors that covered the hilal at the western horizon at the time of observation. The title of this research is The Impact of Clouds on the Visibility of Hilal in Blang Tiron Hill Pole Complex Housing PT. Perta Arun Gas Lhokseumawe with two formula problems namely: 1. How is the category and characteristics of clouds in the horizon of Blang Tyron POB. 2. The impact of the cloud on the visibility of hilal at Blang tiron. In conducting research, the author uses qualitative methods using field research. The primary data sources are observations and interviews with the relevant parties, while the secondary data is documents, books, research journals and related articles. The data collection methods used are observation methods, interviews and documentation studies. The results of this study show that clouds are the factor that covers the hilal in the POB Blang tyron at the time of observations of Ramadan, Shawal, Zulqaidah and Zulhijjah are low clouds of cumulus clouds, medium clouds altostratus, and high clouds comulunimbus and cirrus. The thick clouds that are evenly in the western part of the horizon can release light that divides the brightness of the light that covers the hill, making it difficult for the observers to observe its appearance even though the hills are above the horizont.